Demographic, clinical, laboratory data, prognostic, and treatment features of patients with antisynthetase syndrome: An international, two-center cohort study - Lila Morena Bueno Da Silva,; Upendra Rathore,; Vikas Agarwal,; Latika Gupta,; Samuel Katsuyuki Shinjo, (Archives of Rheumatology, 2022)
Objectives: To compare clinical, demographic, laboratory data, prognostic and treatment characteristics of patients with antisynthetase syndrome (ASSD) treated in two different centers of India and Brazil. Patients and methods: This international, two-center, retro-prospective cohort study which was conducted at two tertiary rheumatology centers (one in Brazil and one in India) between January 2000 to January 2020 included a total of 115 patients with ASSD (21 males, 94 females; mean age; at disease diagnosis at 40.3; range, 18 to 80 years). Demographic, clinical and laboratory data of the patients were recorded. Clinical involvement was evaluated. Results: Of the patients, 81 were Brazilians and 34 were of Indian origin. The Indian group exhibited a greater delay in diagnosis after the onset of symptoms compared to Brazilian patients (12 vs. 6 months, respectively; p=0.026). Brazilian patients exhibited a significantly higher prevalence of joint and lung involvement, mechanic’s hands, and Raynaud’s phenomenon. Anti-Jo-1 was the most common autoantibodies in both groups. Systemic arterial hypertension, followed by diabetes mellitus were the most prevalent comorbidities. Concerning previously used drugs, the Indian patients had a larger group of patients treated with antimalarials, whereas the Brazilian group used more azathioprine and intravenous immunoglobulin. A higher proportion of Indian patients was treated with one immunosuppressive drug (70.6%), while the Brazilian group were often treated using two immunosuppressive drugs (33%). Comparison between the severity and prognosis showed that Brazilian group had a higher number of relapses, and during follow-up, the global mortality rates were similar in both groups (6.2% for Brazilian vs. 8.8% for Indian). Conclusion: Brazilian and Indian patients with ASSD have comparable epidemiological characteristics such as age at the time of disease diagnosis, and sex distribution, and autoantibodies. Diagnostic delay is seen in Indian patients, and Brazilians exhibit a higher prevalence of joint and lung involvement, mechanic’s hands, Raynaud’s phenomenon with a higher number of relapses, although the mortality rate seems to be similar in both groups.